2023
DOI: 10.1111/1346-8138.16967
|View full text |Cite
|
Sign up to set email alerts
|

Patients with keratinization disorders due to ABCA12 variants showing pityriasis rubra pilaris phenotypes

Takuya Takeichi,
Takahiro Hamada,
Mayuko Yamamoto
et al.

Abstract: Pathogenic variants in ABCA12 are important causative genetic defects for autosomal recessive congenital ichthyoses (ARCI), which include congenital ichthyosiform erythroderma (CIE), harlequin ichthyosis, and lamellar ichthyosis. In addition, pathogenic variants in ABCA12 are known to cause a localized nevoid form of CIE due to recessive mosaicism. We previously reported siblings who carried an ABCA12 variant but did not show a “congenital” phenotype. They were considered to have pityriasis rubra pilaris (PRP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…They concluded that the mild phenotype resembling EKVP of their patients was due to a partial loss of function of ABCA12, leading to a partial depletion of GlcCer deposition in the stratum corneum 22 . In these two papers by Takeichi et al 21 . and Terrinoni et al., 22 the identical pathogenic missense variant, c.4601C>T p.(Thr1534Met), located within the first ATP‐binding cassette, was identified both in patients with the PRP‐like phenotype and in patients with the EKVP‐like phenotype.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…They concluded that the mild phenotype resembling EKVP of their patients was due to a partial loss of function of ABCA12, leading to a partial depletion of GlcCer deposition in the stratum corneum 22 . In these two papers by Takeichi et al 21 . and Terrinoni et al., 22 the identical pathogenic missense variant, c.4601C>T p.(Thr1534Met), located within the first ATP‐binding cassette, was identified both in patients with the PRP‐like phenotype and in patients with the EKVP‐like phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…and Terrinoni et al., 22 the identical pathogenic missense variant, c.4601C>T p.(Thr1534Met), located within the first ATP‐binding cassette, was identified both in patients with the PRP‐like phenotype and in patients with the EKVP‐like phenotype. The other causative ABCA12 variant in a patient with the PRP‐like phenotype was located within the second ATP‐binding cassette 21 . The siblings with the EKVP‐like phenotype were compound heterozygous for c.4601C>T p.(Thr1534Met) and a missense variant in the first ATP‐binding cassette 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations